Molecular and modular intricacies of precision oncology - Chhabra, Ravneet (Frontiers in Immunology, 2024)
Precision medicine is revolutionizing the world in combating different disease modalities, including cancer. The concept of personalized treatments is not new but modeling it into a reality has faced various limitations. The last decade has seen significant improvements in incorporating several novel tools, scientific innovations and governmental support in precision oncology. However, the socioeconomic factors and risk-benefit analyses are important considerations. This mini review includes a summary of some commendable milestones, which are not just a series of successes, but also a cautious outlook to the challenges and practical implications of the advancing techno-medical era.